2015
DOI: 10.2147/ijn.s78331
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and bone regeneration of porous nano-hydroxyapatite/coralline blocks coated with rhVEGF165 in critical-size alveolar bone defects in vivo

Abstract: To improve the regenerative performance of nano-hydroxyapatite/coralline (nHA/coral) block grafting in a canine mandibular critical-size defect model, nHA/coral blocks were coated with recombinant human vascular endothelial growth factor 165 (rhVEGF) via physical adsorption (3 μg rhVEGF 165 per nHA/coral block). After the nHA/coral blocks and VEGF/nHA/coral blocks were randomly implanted into the mandibular box-shaped defects in a split-mouth design, the healing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 45 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…The main characteristics of the defect treated, bone graft material characteristics, study outcome, and follow-up time for each animal model are summarized in Table 1, Table 2, Table 3, Table 4, Table 5 and Table 6. Thirty-seven studies (97.3%) performed histologic evaluation of the samples retrieved [18,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60], 26 studies (68.4%) reported histomorphometric analysis, 1 study performed fluorescence microscopy analyses of bone samples [18]. Two studies [47,56] described a scanning electron microscope (SEM) evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of the defect treated, bone graft material characteristics, study outcome, and follow-up time for each animal model are summarized in Table 1, Table 2, Table 3, Table 4, Table 5 and Table 6. Thirty-seven studies (97.3%) performed histologic evaluation of the samples retrieved [18,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60], 26 studies (68.4%) reported histomorphometric analysis, 1 study performed fluorescence microscopy analyses of bone samples [18]. Two studies [47,56] described a scanning electron microscope (SEM) evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven articles [28,29,30,31,32,39,40,51,54,59,61] also performed microcomputed tomography (micro-CT), five a radiographic assessment [18,38,44,55,62], and one article [50] reported an angiogram evaluation. One study also reported X-ray diffraction evaluation [42]. An analytic description of the evaluation techniques is provided in Table 1, Table 2, Table 3, Table 4, Table 5 and Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility for generating blood vessels in the scaffold is to use recombinant pro-angiogenic growth factors such as, VEGF, PDGF, IGF, or TGF-β1 & TGF-β2 adsorbed into the scaffold [502,509]. These proteic substances are difficult to manage and manipulate, expensive and would require a complex authorization and quality control.…”
Section: Rigorous In Vitro Testing Of Bioactive Materialsmentioning
confidence: 99%
“…The histological evaluation and the histomorphometric analysis revealed enhanced neovascular density and a larger quantity of new bone formation at 3 and 8 weeks postsurgery. The results suggest that nHA/coral blocks might be satisfactory scaffolds for block grafting in critical-size mandibular defects and that additional VEGF coating via physical adsorption can promote angiogenesis in the early stage of bone healing [164,165]. 6.1.1.4.…”
Section: Coral-derived Bone Grafts Substitutesmentioning
confidence: 99%